Insights into Teacher Language Awareness with Reference to the Concept of Self-Marginalization and Empowerment in the Use of a Foreign Language - Lankiewicz, Hadrian; Wąsikiewicz-Firlej, Emilia; Szczepaniak-Kozak, Anna (Uniwersytet w Granadzie, 2016)
The concept of self-marginalization and empowerment in applied linguistics can be derived from the so-called critical school, whose sociolinguistic findings pertain to power (Fairclough 1989, 1992) and hegemony (Gramsci, 1971/1991). It offers new perspectives for the perception of a second/foreign language acquisition process. Thereby, with reference to the notions of multicompetence (Cook, 1991), plurilingualism and multilingualism (Kramsch, 2008), metrolingualism (Otsuji & Pennycook, 2010; Pennycook, 2010), the concept of English as a Lingua Franca (Jenkins, 2007), translingual practice (Canagajarah, 2013), and particularly the ecological metaphor in language acquisition (Kramsch, 2002a) and learning (van Lier, 2004), which demystify linguistic normativity, we offer a survey study into the teacher language awareness pertaining to their self-perception as language users. The article concludes with implications for foreign language teacher education in the era of globalization and autonomization of the language learning process.

Los conceptos de automarginalización y empoderamiento en la lingüística aplicada pueden extraerse de las corrientes críticas así denominadas y cuyos resultados sociolingüísticos se refieren al poder (Fairclough, 1989, 1992) y la hegemonía (Gramsci, 1971/1991). Ofrecen nuevas perspectivas para la percepción del proceso de adquisición de una lengua extranjera. Así, asumiendo las ideas de multicompetencia (Cook, 1991), pluringüismo y multilingüismo (Kramsch, 2008), metrolingüismo (Otsuji y Pennycook, 2010; Pennycook, 2010), el concepto de lingua franca (Jenkins, 2007), la práctica translingüística (Canagajarah, 2013), y en particular, la metáfora ecológica en adquisición (Kramsch, 2002a) y aprendizaje de una lengua (van Lier, 2004), que desmitifica la normatividad lingüística, este trabajo ofrece un estudio evaluativo sobre la sensiblilización/concienciación lingüística del profesorado en cuanto a su autopercepción como usuarios de una lengua. El artículo concluye con las implicaciones en la educación del profesorado de lengua extranjera en la era de la globalización y de la autonomización del proceso de aprendizaje de lenguas.
Keywords: teacher language awareness; marginalization; empowerment; linguistic normativity; autonomization